VIOLENCE IN THE NAME OF RELIGION FROM THE PERSPECTIVE OF PHILOSOPHY OF LAW - Muhammad Solikhudin; Sheyla Nichlatus Sovia (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
Violence in the name of religion seems to be being carried out by all groups of Indonesian society. Even in some cases, there are strong nuances to amplify the desecration. Religion that is not inclusive with one-sided truth claims still shows its existence which is quite strong among religious people, especially Muslims. They consider their religious understanding to be an undeniable truth, and is considered a definite reflection of the source of religious teachings. This brings religious people to a life where conflicts often occur between fellow human beings, both fellow believers of same religion but different sects, as well as fellow believers of different religions. In addition, understanding this model will make religious people fall into an extreme religious understanding. Religion is understood as dead dogmas and only deals with the problems of the hereafter and divinity so that it does not have the ability to provide pleasant solutions in solving human problems that are manifested in today's life. This article tries to analyze the problems above by using a philosophy of law approach so that the reader is able to see the problem with an objective view without losing common sense. Keywords: Religious Violence, Indonesia, The Philosophy of Law. Abstrak Kekerasan atas nama agama hingga saat ini tampaknya masih terus dilakukan segenap kelompok dari masyarakat Indonesia. Bahkan pada sebagian kasus, ada nuansa kuat untuk menguatkan penodaan tersebut. Keberagamaan yang tidak inklusif dengan klaim kebenaran sepihak masih menampakkan keberadaannya yang cukup kuat di kalangan umat beragama, khususnya umat Islam. Mereka menganggap pemahaman keagamaan yang dianut mereka merupakan kebenaran yang tidak terbantah, serta dianggap pencerminan yang pasti dari sumber ajaran agama. Hal ini membawa umat beragama kepada kehidupan yang sering terjadi konflik antar sesama manusia, baik sesama pemeluk agama yang berbeda aliran, maupun sesama umat yang berbeda agama. Di samping itu, pemahaman model itu akan membuat umat beragama masuk dalam pemahaman keagamaan yang ekstrim. Agama dipahami sebagai dogma-dogma mati dan hanya mengurus masalah akhirat serta ketuhanan sehingga tidak memiliki kemampuan untuk memberikan solusi yang menyenangkan dalam penyelesaian problem kemanusiaan yang terwujud di kehidupan masa kini. Artikel ini mencoba menganalisis permasalahan di atas dengan menggunakan pendekatan filsafat hukum sehingga pembaca mampu melihat permasalahan tersebut dengan pandangan objektif tanpa kehilangan akal sehat. Kata Kunci: Kekerasan Agama, Indonesia, Filsafat Hukum.